Validation of the diagnosis of necrotising enterocolitis in a Swedish population‐based observational study. (9th October 2018) - Challis, Pontus; Larsson, Linn; Stoltz Sjöström, Elisabeth; Serenius, Fredrik; Domellöf, Magnus; Elfvin, Anders
Abstract: Aim: The definition of necrotising enterocolitis (NEC) is based on clinical and radiological signs that can be difficult to interpret. The aim of the present study was to validate the incidence of NEC in the Extremely Preterm Infants in Sweden Study (EXPRESS) Methods: The EXPRESS study consisted of all 707 infants born before 27 + 0 gestational weeks during the years 2004–2007 in Sweden. Of these infants, 38 were recorded as having NEC of Bell stage II or higher. Hospital records were obtained for these infants. Furthermore, to identify missed cases, all infants with a sudden reduction of enteral nutrition, in the EXPRESS study were identified (n = 71). Hospital records for these infants were obtained. Thus, 108 hospital records were obtained and scored independently by two neonatologists for NEC. Results: Of 38 NEC cases in the EXPRESS study, 26 were classified as NEC after validation. Four cases not recorded in the EXPRESS study were found. The incidence of NEC decreased from 6.3% to 4.3%. Conclusion: Validation of the incidence of NEC revealed over‐ and underestimation of NEC in the EXPRESS study despite carefully collected data. Similar problems may occur in other national data sets or quality registers. Abstract :